High fibrinogen‐to‐albumin ratio is associated with hemorrhagic transformation in acute ischemic stroke patients. Issue 1 (12th December 2020) - Ruan, Yiting; Yuan, Chengxiang; Liu, Yuntao; Zeng, Yaying; Cheng, Haoran; Cheng, Qianqian; Chen, Yunbin; Huang, Guiqian; He, Weilei; He, Jincai
Abstract: Introduction: Hemorrhagic transformation (HT) is a complex and multifactorial complication among patients with acute ischemic stroke (AIS), and the inflammatory response has been considered as a risk factor for HT. We aimed to evaluate the stratification of FAR (fibrinogen‐to‐albumin ratio), an inflammatory biomarker, in HT patients. Methods: A total of 256 consecutive stroke patients with HT and 256 age‐ and gender‐matched stroke patients without HT were included in this study. HT during hospitalization was diagnosed by follow‐up imaging assessment and was classified into hemorrhagic infarction (HI) and parenchymal hematoma (PH) according to the recommendations of European Cooperative Acute Stroke Study II classification. Blood samples were obtained at admission. Results: Higher levels of FAR were observed in patients with HT compared with the non‐HT group [10.29 (8.39–12.95) vs. 8.60 (7.25–10.8), p  < .001], but no significant difference was found between the PH and HI [10.88 (8.72–13.40) vs. 10.13 (8.14–12.60), p  > .05]. Patients were assigned to groups of high FAR (≥9.51) and low FAR (<9.51) based on the optimal cut‐off value. After adjustment for potential confounders, the high FAR remained independently associated with the increased risk of HT (OR = 5.027, 95% CI = 5.027 (2.309–10.942), p  < .001). Conclusions: High FAR was independently associated with the increased risk of HT after AIS. Abstract : This study is the first to explore the association between fibrinogen‐to‐albumin ratio (FAR) and hemorrhagic transformation (HT) in acute ischemic stroke patients. We observed that FAR was associated with HT. The calculation of FAR may assist clinicians identify patients at elevated risk of HT and make better‐informed individualized treatment.